2020
DOI: 10.37104/ithj.v3i1.45
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Senam Kaki Terhadap Penyembuhan Luka Diabetik Pada Pasien Diabetes Mellitus Di Ruang Rawat Inap Ra1 Dan Ra2 Penyakit Dalam Rsup. H. Adam Malik Medan

Abstract: Diabetic foot ulcers (DFUs) are a serious complication of diabetes mellitus (DM) that can be slow to heal, result in repeated hospitalizations, require intense and costly treatment, and reduce the quality of life. The purpose of this study was to investigate the effect of foot exercises on wound healing in type 2 diabetic patients with a diabetic foot ulcer. Quasi-experimental study using before and after changes to wound healing in between February until May 2019.Thirty patients from an inpatient rooms with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This proved by several studies that found blood glucose level gradually decreased after getting this exercise (Graciella & Prabawati, 2020;Haskas et al, 2023). This better regulation of blood glucose then improve wound healing process among patients (Pasaribu & Sebayang, 2020) An interesting aspect of providing diabetes foot exercises is that they not only provide physical benefits but also offer psychological benefits related to comfort during religious rituals. They help patients become more independent in maintaining the cleanliness and functionality of their feet.…”
Section: Outcomes Of Diabetic Foot Exercisesmentioning
confidence: 93%
“…This proved by several studies that found blood glucose level gradually decreased after getting this exercise (Graciella & Prabawati, 2020;Haskas et al, 2023). This better regulation of blood glucose then improve wound healing process among patients (Pasaribu & Sebayang, 2020) An interesting aspect of providing diabetes foot exercises is that they not only provide physical benefits but also offer psychological benefits related to comfort during religious rituals. They help patients become more independent in maintaining the cleanliness and functionality of their feet.…”
Section: Outcomes Of Diabetic Foot Exercisesmentioning
confidence: 93%